2020
DOI: 10.1371/journal.pone.0232284
|View full text |Cite
|
Sign up to set email alerts
|

In silico analyses identify lncRNAs: WDFY3-AS2, BDNF-AS and AFAP1-AS1 as potential prognostic factors for patients with triple-negative breast tumors

Abstract: Background Long non-coding RNAs (lncRNAs) are characterized as having 200 nucleotides or more and not coding any protein, and several been identified as differentially expressed in several human malignancies, including breast cancer. Methods Here, we evaluated lncRNAs differentially expressed in triple-negative breast cancer (TNBC) from a cDNA microarray data set obtained in a previous study from our group. Using in silico analyses in combination with a review of the current literature, we identify three lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…Limited knockout of AFAP1-AS1 (about 25–50%) is sufficient to reduce proliferation and colony formation of MDA–MB-231 and HCC1937 cells [ 16 ], meanwhile AFAP1-AS1 knockdown also represses BT-549 and MCF-7 cell proliferation and migration by downregulating septin-2 ( SEPT2 ) via the sponging of miR-497-5p [ 17 ]. An in silico analysis of cDNA microarray data confirmed that AFAP1-AS1 is a potential prognostic factor in TNBC [ 18 ]. In addition, it promotes EMT via the Wnt / β-catenin signaling pathway in TNBC [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limited knockout of AFAP1-AS1 (about 25–50%) is sufficient to reduce proliferation and colony formation of MDA–MB-231 and HCC1937 cells [ 16 ], meanwhile AFAP1-AS1 knockdown also represses BT-549 and MCF-7 cell proliferation and migration by downregulating septin-2 ( SEPT2 ) via the sponging of miR-497-5p [ 17 ]. An in silico analysis of cDNA microarray data confirmed that AFAP1-AS1 is a potential prognostic factor in TNBC [ 18 ]. In addition, it promotes EMT via the Wnt / β-catenin signaling pathway in TNBC [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have reported that various lncRNAs modulates the progression of TNBC, and aberrant expression of lncRNAs worsen the disease (Figure 7) (C. Chen et al, 2015; B. Guo et al, 2020; Le et al, 2019; Naorem et al, 2020; Rodrigues de Bastos & Nagai, 2020). A detailed list of lncRNAs that are associated with TNBC development and progression are mentioned in Table 1, along with their respective mechanisms or outcomes (Table 2) (Ang et al, 2020; Ge et al, 2020).…”
Section: Lncrnas Associated With Tnbcmentioning
confidence: 99%
“…Limited knockout of AFAP1-AS1 (about 25-50%) was su cient to reduce the proliferation and colony formation in MDA-MB-231 cells and HCC1937 cells [16] , meanwhile repressed BT-549 and MCF-7 cells proliferation, migration by downregulating SEPT2 via sponging miR-497-5p [17] . An in silico analysis from cDNA microarray data con rmed that AFAP1-AS1 was potential prognostic factor for TNBC patients [18] . And it promoted epithelial-mesenchymal transition by Wnt/β-catenin signaling pathway in TNBC [19] .…”
Section: Introductionmentioning
confidence: 99%